2020
DOI: 10.1088/1475-7516/2020/11/016
|View full text |Cite
|
Sign up to set email alerts
|

Informing dark matter direct detection limits with the ARTEMIS simulations

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 99 publications
1
6
0
Order By: Relevance
“…We have also shown that including baryons (with or without DM self-interactions) in the simulations has a major effect on the local DM distribution. This agrees with the results of previous work, which compared the local DM distributions in CDM (including baryons) and DM-only halos in various high resolution cosmological simulations [37][38][39][40][41][42].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have also shown that including baryons (with or without DM self-interactions) in the simulations has a major effect on the local DM distribution. This agrees with the results of previous work, which compared the local DM distributions in CDM (including baryons) and DM-only halos in various high resolution cosmological simulations [37][38][39][40][41][42].…”
Section: Discussionsupporting
confidence: 92%
“…The local DM density in the SHM is assumed to be 0.3 or 0.4 GeV/cm 3 and the local velocity distribution is assumed to be a Maxwellian distribution in the Galactic rest frame, with a peak speed equal to the local circular speed, v c , usually set equal to 230 km/s, and truncated at an escape speed of 544 km/s from the Galaxy. Recent cosmological simulations of ΛCDM including baryons have provided realistic predictions for the local DM distribution and its implications for DM direct detection [37][38][39][40][41][42]. These studies find that a Maxwell-Boltzmann distribution provides a good fit to the local DM velocity distribution of MW-like halos in ΛCDM simulations.…”
Section: Introductionmentioning
confidence: 85%
“…Appendix A Figure 1 References Apart from Symphony, Figure 1 shows the following cosmological zoom-in simulations: NIHAO (Wang et al 2015;Dutton et al 2016), ELVIS (Garrison-Kimmel et al 2014, 2019, Artemis (Poole-McKenzie et al 2020), Caterpillar (Griffen et al 2016), Via Lactea (Diemand et al 2008), Aquarius (Springel et al 2008), Latte (Wetzel et al 2016;Samuel et al 2020), APOSTLE (Sawala et al 2016), Ponos (Fiacconi et al 2016(Fiacconi et al , 2017, Phoenix (Gao et al 2012), the Three Hundred Project (Cui et al 2018), C-EAGLE (Barnes et al 2017), and simulations from Despali et al (2019) and Richings et al (2020). This collection is not comprehensive, and does not include: resimulation suites (e.g., PhatELVIS; Kelley et al 2019), zoom-ins of cosmological volumes that do not target specific hosts (e.g., Copernicus Complexio; Hellwing et al 2016), hydrodynamic simulations of lower-mass galaxies (e.g., from FIRE; Hopkins et al 2014), or simulations only presented in a hydrodynamic context (e.g., ERIS; Guedes et al 2011).…”
Section: Appendix B Convergence Testsmentioning
confidence: 99%
“…First, the majority of cosmological zoom-in simulations focus on host halos with masses similar to the Milky Way (e.g., Diemand et al 2008;Springel et al 2008;Garrison-Kimmel et al 2014;Mao et al 2015;Griffen et al 2016;Sawala et al 2016;Wetzel et al 2016;Samuel et al 2020;Poole-McKenzie et al 2020) or galaxy clusters (e.g., Gao et al 2012; Barnes et al 2017;Cui et al 2018). Although many exceptions exist (e.g., Wang et al 2015;Dutton et al 2016;Fiacconi et al 2016Fiacconi et al , 2017Despali et al 2019;Richings et al 2021), zoom-in suites at other mass scales typically include only a few distinct hosts, precluding analyses of their subhalo populations that capture host-tohost scatter (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The suite comprises 45 such systems and their retinue of dwarf galaxies. The simulations have previously been shown to match a range of global properties of Milky Way-mass galaxies, such as galaxy sizes, star formation rates, stellar metallicities, and various observed properties of Milky Way-mass stellar haloes (Font et al 2020) and of the solar neighborhood (Poole-McKenzie et al 2020).…”
Section: Introductionmentioning
confidence: 99%